(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article examines modern methods of literary text analysis in philology. Particular attention is paid to cognitive, discourse, structural and hermeneutic approaches to the study of literary works. The possibilities of modern methods in developing critical thinking, analytical skills and research competence of philology students are analyzed. The results show that a comprehensive analysis of literary texts contributes to a deeper understanding of literary works and improves students’ professional training.